Characterization of the primary and secondary crystallization kinetics of a linear low-density polyethylene in quiescent- and flow-conditions. (12th October 2015) - van Drongelen, M.; Roozemond, P.C.; Troisi, E.M.; Doufas, A.K.; Peters, G.W.M.
Abstract: The primary and secondary crystallization kinetics of a homogeneous linear low-density polyethylene were characterized as function of cooling rate, pressure and flow strength. Our approach to describe primary crystallization is based on nucleation and growth of spherulites, quantified well below the melting temperature using small-angle light scattering. The description of the two-step secondary process is coupled to primary crystallization using a convolution integral, for which the parameters were determined from (fast-) differential scanning calorimetry. Extended-dilatometry was used to investigate the effect of different thermomechanical histories. Parameters were determined for an existing model that couples molecular stretch to both nucleation rate and fibrillar growth rate. Excellent agreement is shown between calculated and experimentally obtained crystallization kinetics in conditions representative for those found in real-life processing conditions. This opens the possibility to calculate in detail the evolution of and the final crystallinity structure in products such as blown film or extruded tape. Graphical abstract: Highlights: A peak decomposition method was applied to distinguish multiple crystallization processes in a range of 0.07–2000 °C/s. The nucleation density and growth rate were measured and able to describe the measured kinetics of primary crystallization. Using a convolution integral approach, secondary crystallization was also implemented in the crystallization model. As expected, flow promotes primary crystallization, although it clearly reduces secondary crystallization. The stretch-based XPP model was used to describe the experimentally obtained (flow-induced) primary crystallization kinetics.